The compound effects of conflict and disaster displacement in Bosnia and Herzegovina - Turner, W (Refugee Studies Centre, University of Oxford, 2015)
Some IDPs living in protracted displacement in Bosnia and Herzegovina, such as many Roma IDPs, were especially vulnerable to the effects of the May 2014 flooding and landslides